Anxiety in Multiple Sclerosis: psychometric properties of the State‐Trait Anxiety Inventory. (1st February 2016) - Santangelo, G.; Sacco, R.; Siciliano, M.; Bisecco, A.; Muzzo, G.; Docimo, R.; De Stefano, M.; Bonavita, S.; Lavorgna, L.; Tedeschi, G.; Trojano, L.; Gallo, A.
Abstract : Objective: The aims of the present study were to examine psychometric properties of the Spielberger State‐Trait Anxiety Inventory (STAI‐Y‐1 and STAI‐Y‐2, respectively) in a Multiple Sclerosis (MS) population and to identify a cut‐off score to detect those MS patients with high level of state and/or trait anxiety who could be more vulnerable to development of depression and/or cognitive defects. Material and methods: The STAI‐Y‐1 and STAI‐Y‐2 was completed by a group of patients ( n = 175) affected by MS and a group of healthy subjects ( n = 150) matched for age, educational level, and gender. In MS patients internal consistency, divergent and discriminant validities were evaluated. Construct validity was examined by exploratory factor analysis for each scale. Results: There was no missing data, no floor or ceiling effects for both scales. The two scales showed high internal consistency, good divergent, and Known‐groups validities. To identify high levels of state and trait anxiety in a patient with MS, we proposed three gender specific screening cut‐off values (1, 1.5, 2 SD) for the STAI‐Y‐1 and the STAI‐Y‐2. Conclusions: The findings showed that the STAI‐Y‐1 and the STAI‐Y‐2 are a valid tool for clinical use in MS patients and can be useful to measure the severity of anxiety and to identify those patients with high anxiety to introduce them in specific non‐pharmacological intervention.